Carta de Luis Porrata Doria a Roberto H. Todd - Porrata Doria, Luis; Todd, Roberto H. (My University, 1939)
Rectificaciones de un artículo alusivo a Herminio Díaz Navarro
Keywords: Coll Cuchi, Víctor; Diaz Navarro, Herminio; Baldorioty de Castro, Román, 1822-1889; Partido Autonomista Puertorriqueño